2022
DOI: 10.3389/fpsyt.2022.986389
|View full text |Cite
|
Sign up to set email alerts
|

The major risk factor for depression in the Chinese middle-aged and elderly population: A cross-sectional study

Abstract: BackgroundThe number of patients suffering from depression is continuously increasing in China. Demographic characteristics, physical health levels, and individual lifestyles/healthy behaviors are associated with the severity of depression. However, the major risk factor for depression remains unclear.Materials and methodsIn this investigation, 16,512 patients were screened using the CHARLS (China Health and Retirement Longitudinal Study) database after being determined to be eligible based on the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In older age, Blazer et al conducted a study in the United States and found that the prevalence of depression tended to decrease with age, although it remained a significant concern, particularly in the context of other physical and mental health conditions that are more common in older age [ 11 ]. Another study conducted in China found that depression in older adults was often accompanied by cognitive and physical symptoms, such as memory problems and fatigue, and may be more difficult to diagnose and treat due to overlapping symptoms with other conditions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In older age, Blazer et al conducted a study in the United States and found that the prevalence of depression tended to decrease with age, although it remained a significant concern, particularly in the context of other physical and mental health conditions that are more common in older age [ 11 ]. Another study conducted in China found that depression in older adults was often accompanied by cognitive and physical symptoms, such as memory problems and fatigue, and may be more difficult to diagnose and treat due to overlapping symptoms with other conditions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the most common mental disorders, affecting nearly 3.8% of the global population [5] , and is a major contributor to the global burden of disease and a leading cause of disability, and is an important public health problem worldwide.In China, a national survey reported that about 30% of men and 43% of women aged 45 and older experienced depressive symptoms [6] .Many studies have demonstrated that ACEs function in the life course on depression susceptibility [7][8] . With the accelerated population aging, understanding the factors and the underlying mechanisms that may increase the risk of depression in middle-aged and older adults has become an important public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of older adults will suffer from one or more age-related diseases, including two significant conditions that can cause high morbidity and disability, with high economic burden consequences: stroke (1) and depression (2). Stroke is divided into ischemic stroke and hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%